Avaliação do Protocolo de Entrevista Investigativa NICHD em contexto análogo ao forense - Hackbarth, Chayene (Universidade Federal de São Carlos, 2019)
Child sexual abuse is a public health problem that presents challenges for the Judiciary system given the difficulty in presenting evidence to substantiate it. This study joins other Brazilian studies testing the applicability of the NICHD Protocol, from the National Institute of Child Health and Human Development, for the investigation of alleged child sexual abuse cases in this context. This is a pioneer analogous study to the forensic setting in Brazil which replicates an international study to evaluate the quality of the interviews conducted with the protocol by interviewers trained by the author. The objectives of the study were: 1) to evaluate the accuracy of the information provided by children according to the different modalities of questions present in the NICHD protocol (open, direct, multiple, suggestive and suggestive questions), comparing interviews about a staged target event with a group of children who were interviewed with the pre-substantive phase of NICHD protocol (PSG) and a comparison group with interviewers without the pre-substantive training (CG); and 2) to verify the proportion with which children in these two conditions reported, when asked, to have participated in a fictitious event that never took place. It is hypothesized that as in the original study, the group of children who went through the pre-substantive training interviewers had superior performance in narrative practice and number of relevant details about the target event, being more resistant to interviewer's suggestive questions about the fictitious event than the control group. 108 children (51 boys and 57 girls) were interviewed in four public schools in Mato Grosso State, Brazil regarding a staged event by the researchers. The information was coded for comparison with statistical tests, such as Kruskal-Wallis non-parametric test and U de Mann-Whitney test for comparison of two proportions. Results indicated that the number of questions for the CG was significantly higher than for the PSG, contrary to the hypothesis regarding the extension of information presented in the children's responses when using the pre-substantive phase of the NICHD Protocol. Possibly due to the inexperience of the interviewers (undergraduate students) and their short training there was insufficient investment in the pre-substantive phase without extensive use of open-ended questions for appropriate narrative training, as recommended. However, incorrect reports about the fictitious event were more frequent in the CG, showing that the rapport training seems to have been effective in preparing the children to resist suggestive questions about the fictitious event, corroborating the literature about children’s abilities to differentiate truth from lies and make reliable accounts of their experiences, resisting the interviewer's suggestive questions.
Evaluation of NICHD investigative interview protocol in an analogous forensic context
Keywords: Abuso sexual infantil; Oitiva de crianças; Protocolo NICHD; Child sexual abuse; Children testimony; NICHD protocol; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA COGNITIVA